Forests and Rural Development - Pretzsch, Jürgen; Darr, Dietrich; Uibrig, Holm.; Auch, Eckhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book provides an overview of the complex challenges and opportunities related to forest-based rural development in the tropics and subtropics. Applying a socio-ecological perspective, the book traces the changing paradigms of forestry in rural development throughout history, summarizes the major aspects of the rural development challenge in forest areas, and documents innovative approaches in fields such as land utilization, technology and organizational development, rural advisory services, financing mechanisms, participative planning, and forest governance. It brings together scholars and practitioners dealing with the topics from various theoretical and practical angles. Calling for an approach that carefully balances market forces with government intervention, the book shows that forests in rural areas have the potential to provide a solid foundation for a green global economy.
Introduction -- Paradigms -- The Challenges Facing Forest-Based Rural Development in the Tropics and Subtropics -- Land Management Systems at the Interface Between Forestry and Agriculture -- Organizational Changes in Forest Management -- Creating Rural Employment and Generating Income in Forest-Based Value Chains -- At the Interface of Culture, Development and Forests: Insights from Bolivia and Kenya -- Extension Services for Rural Development -- Payment Schemes for Environmental Services – Challenges and Pitfalls with Respect to Effectiveness, Efficiency and Equity -- Financing Forests for Rural Development -- Land Use Planning for Sustainable Forestry -- Forest Governance and Sustainable Rural Development -- Prospects for Forest-Based Rural Development.
Keywords: Forestry management; Agriculture; Forestry; Forestry Management; Agriculture; Forestry